Sensitivity and Specificity of Pulse Oximetry for Congenital Heart Disease Screening in Newborn: A Meta-Analysis - Ilma Syifannisa; Raden Ayu Libert Gatho Reza Valentine; Dodo Islamuddin Khomara Rangkuti (GHMJ (Global Health Management Journal))
Background: Early detection for Congenital Heart Disease (CHD) using pulse oximetry is a routine procedure for newborn. Pulse Oximetry Screening (POS) has been shown to be effective in detecting CHD.